(untitled) (Journal of Medicine, 2017)
Epistaxis although is a common presentation that seldom require surgical intervention, it is still consider as an emergency. We report a case of 26 years old gentleman with atraumatic intractable anterior epistaxis after recent history of vaping. Purpose of this case report is to highlight the flow of management of anterior epistaxis. We provide a literature review for the sequence of actions for the management of anterior epistaxis and also a discussion on association between vaping habit and epistaxis. J MEDICINE January 2017; 18 (1) : 44-46